Human Factors and Ergonomics in the Design of Health Information Technology: Trends and Progress in 2014 - Pelayo, S. (Yearb Med Inform, 2015)
OBJECTIVE: To summarize significant contributions to the research on human factors and organizational issues in medical informatics. METHODS: An extensive search using PubMed/Medline and Web of Science® was conducted to identify the scientific contributions, published in 2014, to human factors and organizational issues in medical informatics, with a focus on health information technology (HIT) usability. The selection process comprised three steps: (i) 15 candidate best papers were selected by the two section editors, (ii) external reviewers from a pool of international experts reviewed each candidate best paper, and (iii) the final selection of three best papers was made by the editorial board of the IMIA Yearbook. RESULTS: Noteworthy papers published in 2014 describe an efficient, easy to implement, and useful process for detecting and mitigating human factors and ergonomics (HFE) issues of HIT. They contribute to promote the HFE approach with interventions based on rigorous and well-conducted methods when designing and implementing HIT. CONCLUSION: The application of HFE in the design and implementation of HIT remains limited, and the impact of incorporating HFE principles on patient safety is understudied. Future works should be conducted to advance this field of research, so that the safety and quality of patient care are not compromised by the increasing adoption of HIT.